Analysis of clinical characteristics and risk factors of recurrent Clostridioides difficile infection in children - Jin-Yue Huang; Ning Wang; Jing-Yao Wang; Hua-Chu Zuo; Juan Li; Yu Zhao (Frontiers in Pediatrics)
ObjectiveTo analyze clinical characteristics and risk factors for recurrence of Clostridioides difficile infection (CDI) in children.MethodsClinical data were retrospectively collected from all children (<18 years) hospitalized with CDI at Tianjin Children's Hospital between September 2018 and December 2023.ResultsIn total, 115 patients (66 males and 49 females;) were divided into recurrence (n = 38) and non-recurrence (n = 77) groups. Logistic regression was used to compare clinical data and analyze risk factors for CDI recurrence. The recurrent CDI(rCDI) and non-recurrence groups had statistically significant differences in terms of age, comorbidities, prior antibiotic exposure, mode of CDI acquisition (hospital vs. community), colonoscopy(the rationale for colonoscopy data inclusion—diagnosis confirmation or ruling out other causes), treatment selection, levels of interleukin-6 and creatine kinase, and body mass index (p < 0.05). Multivariate analysis showed that healthcare-associated CDI [odds ratio [OR] = 14.754, 95% confidence interval [CI]:4.568–47.650, p = 0.000] is an independent risk factor for CDI recurrence in children (p < 0.05), with sensitivity and specificity of 73.7% and 87.0%, respectively.ConclusionHealthcare-associated CDI (HA-CDI)is an independent risk factor for pediatric rCDI, and the introduction of this indicator in diagnosis has certain accuracy in predicting rCDI.